2020
DOI: 10.32938/ag.v5i4.1166
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Pandemi COVID-19 terhadap Kinerja Nilai Ekspor Pertanian Indonesia

Abstract: Pandemi coronavirus menyebabkan dunia masuk dalam kondisi krisis baik krisis kesehatan maupun krisis ekonomi. Akibat dari virus ini perdagangan antar negara menjadi terhambat, sebab terjadi lockdown (pembatasan sosial berskala besar) yang mengakibatkan pertumbuhan ekonomi berjalan lambat. Ekspor merupakan salah satu kegiatan perdagangan internasional yang dilakukan oleh Indonesia. Sektor pertanian menyumbang 2,3% dari total ekspor Indonesia, namun sektor pertanian merupakan sektor yang mampu bertahan dalam kea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…This means that agricultural trade can boost inclusive growth. In Indonesia, the impact of the COVID-19 pandemic on agricultural export was examined by Maulana [29], and it was found that the COVID-19 pandemic has had no important effect on agricultural export based on the t-test method, but an important effect was detected when using the F-test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that agricultural trade can boost inclusive growth. In Indonesia, the impact of the COVID-19 pandemic on agricultural export was examined by Maulana [29], and it was found that the COVID-19 pandemic has had no important effect on agricultural export based on the t-test method, but an important effect was detected when using the F-test.…”
Section: Introductionmentioning
confidence: 99%
“…Most previously conducted studies lack generalizability, because the place of study was country-specific, so the results cannot be generalized to other countries. Additionally, according to Maulana [29], data was only examined partially, not simultaneously. This study aimed to fill this gap and determine the contribution of agricultural exports to economic growth during the pandemic situation.…”
Section: Introductionmentioning
confidence: 99%
“…Pandemi ini menyebabkan negara Indonesia masuk dalam kondisi krisis kesehatan dan juga krisis ekonomi. Menurut Subchiandi & Nubatonis (2020) akibat dari pandemi ini pertumbuhan ekonomi berjalan lambat dan semua perdagangan mengalami keterhambatan akibat adanya lockdown PSBB (Pembatasan Sosial Berskala Besar). Sektor pertanian sangat berpengaruh karena berkaitan secara langsung dengan kebutuhan hidup masyarakat di setiap harinya seperti ketersediaan pangan di suatu negara.…”
Section: Pendahuluanunclassified
“…Even in East Java developed agropolitan area. So do not be surprised if in this agricultural sector the performance of export value also experiences an upward trend [11].…”
Section: Introductionmentioning
confidence: 99%